2017
DOI: 10.5005/jp-journals-10018-1235
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Venous Pressure Gradient Measurement in Bangladeshi Cirrhotic Patients: A Correlation with Child's Status, Variceal Size, and Bleeding

Abstract: Background:Hepatic venous pressure gradient (HVPG) reflects the portal pressure in patients with cirrhotic portal hypertension. The aim of the study was to assess the relation of HVPG to variceal size, Child-Pugh status, and variceal bleeding.Materials and methods:A total of 96 patients with cirrhosis of liver were enrolled prospectively and each patient’s HVPG level was measured via the transfemoral route. Clinical and biochemical evaluation and upper gastrointestinal (GI) endoscopy were done in each subject.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
(17 reference statements)
1
4
0
Order By: Relevance
“…According to the findings of the current study, individuals with large varices exhibited significantly higher mean HVPG levels compared to those with small varices or without varices. These results align with a study conducted by Al Mahtab et al [36] in India, where patients with varices demonstrated a notably elevated mean HVPG level (11.7±3.8) compared to those without varices. The statistical analysis revealed a negligible significance of varices when comparing smaller (16.2±4.9 mmHg) and larger (20±7 mmHg) sizes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…According to the findings of the current study, individuals with large varices exhibited significantly higher mean HVPG levels compared to those with small varices or without varices. These results align with a study conducted by Al Mahtab et al [36] in India, where patients with varices demonstrated a notably elevated mean HVPG level (11.7±3.8) compared to those without varices. The statistical analysis revealed a negligible significance of varices when comparing smaller (16.2±4.9 mmHg) and larger (20±7 mmHg) sizes.…”
Section: Discussionsupporting
confidence: 92%
“…There was a moderately significant positive connection between HE grades and HVPG. Since encephalopathy patients were excluded from the studies by Al Mahtab et al [36], Kim et al [33], and Silkauskaite et al [32], other studies have investigated the correlation between HE and HVPG. In contrast to the findings of the current study, Ramanathan et al observed that there was no link between HE and HVPG and that there was not a significant distinction between those with mild encephalopathy and those without encephalopathy in terms of the mean HVPG level [31].…”
Section: Discussionmentioning
confidence: 99%
“…HVPG is the method of choice to evaluate portal hypertension [25] and has been proved to be an independent risk factor of variceal rebleeding [5,6,26]. Therefore, HVPG-guide therapy is probably the most rational approach to prevent variceal rebleeding [2,6,27,28]. HVPG >16 mmHg indicates a higher risk of death [18,29].…”
Section: Discussionmentioning
confidence: 99%
“…HVPG measurement is not compulsory in clinical practice for betablockers to be started[8,11]. Virtually all patients with large oesophageal varices or with small varices and decompensated cirrhosis have an HVPG > 12 mmHg[24,32-35]. The percentage decrease in PH was not evaluated and was therefore not available.…”
Section: Discussionmentioning
confidence: 99%